TUBAL ECTOPIC PREGNANCY AND THE DETERMINANTS OF ITS DIFFERENT TREATMENT OPTIONS - Karim, Rukhsana; Rauf, Bushra (Journal of Postgraduate Medical Institute, 2021)
Objective: To find out the determinants affecting the different management options of tubal ectopic pregnancy. Methodology: This cross sectional study was carried out in the Unit A of the department of obstetrics and gynecology, Hayatabad Medical Complex, Peshawar from December 2014 to March 2018. All the patients admitted with clinical/ultrasound diagnosis of tubal ectopic pregnancy were included in the study through convenient sampling technique after informed consent. Patients having other early pregnancy problems which would mimic tubal ectopic pregnancy and those having any medical contraindications to Methotrexate were excluded. A pre-designed performa was used to collect the data, which was analyzed using SPSS v.22.0. Results: The mean age of the sample (n=78) was 27.0±7.8 years. Maximum patients were multigravida (n=41, 52.6%), followed by primigravida (n=25, 32.0%). In treatment modalities, maximum of the cases (n=43, 55.1%) were managed medically via methotrexate with success rate of 93.0%, while 18 (23.1%) cases were managed conservatively with success rate of 83.3%, and 17 (21.8%) of the cases were managed surgically with 100% success rate. The maximum size of adnexal mass was found to be as 8.6×7, 10×7, and 8×6 in three management options, i.e., conservative, medical and surgical respectively, while in the same categories, maximum Beta-Human Chorionic Gonadotropin (B-hCG) level was found to be as 978, 43220, and 29844 mIU/ml respectively. Conclusion: Hemodynamic instability and rising B-hCG were the core determinants in the management of tubal ectopic pregnancy. The size of the adnexal mass and the initial B-hCG did not affect the management.